Altered Expression of the Malate-Permeable Anion Channel OsALMT4 Reduces the Growth of Rice Under Low Radiance - Liu, Jie; Xu, Muyun; Estavillo, Gonzalo M.; Delhaize, Emmanuel; White, Rosemary G.; Zhou, Meixue; Ryan, Peter R. (Frontiers in Plant Science, 2018)
We examined the function of OsALMT4 in rice (Oryza sativa L.) which a member of the aluminium-activated malate transporter family. Previous studies showed that OsALMT4 localises to the plasma membrane and that expression in transgenic rice lines results in a constitutive release of malate from the roots. Here we show that OsALMT4 is expressed widely in roots, shoots, flowers and grain but not guard cells. Expression was also affected by ionic and osmotic stress, light and to the hormones ABA, IAA and salicylic acid. Malate efflux from the transgenic plants over-expressing OsALMT4 was inhibited by niflumate and salicylic acid. Growth of transgenic lines with either increased OsALMT4 expression or reduced expression was measured in different environments. Light intensity caused significant differences in growth between the transgenic lines and controls. When day-time light was reduced from 700 to 300 µmol m-2s-1 independent transgenic lines with either increased or decreased OsALMT4 expression accumulated less biomass compared to their null controls. This response was not associated with differences in photosynthetic capacity, stomatal conductance or sugar concentrations in tissues. We propose that by disrupting malate fluxes across the plasma membrane carbon partitioning and perhaps signaling are affected which compromises growth under low light. We conclude that OsALMT4 is expressed widely in rice and facilitates malate efflux from different cell types. Altering OsALMT4 expression compromises growth in low-light environments.